Comparison of Pt/C Electrocatalyst Deposition Methods for PEM Fuel Cells - Vincenzo Palma; Vincenzo Vaiano; Mariantomietta Matarangolo; Gaetano Anello (Chemical Engineering Transactions, 2018)
In recent years, in order to solve the environmental problems associated with electricity production, alternative systems to traditional methods have been developed. In this contest, fuel cells are widely considered to be an efficient and non-polluting power source and therefore, they are considered to be promising energy devices for the transport, mobile, and stationary sectors. At the current stage of technology, among different types of developed fuel cells, proton exchange membrane fuel cells (PEM) deserve major attention. Pt/C deposited on Nafion membrane is the most used electrocatalyst for PEM due to the highest oxygen reduction catalytic activity. The most used conventional deposition methods on Nafion polymeric membranes for commercial PEM are screen printing and transfer printing. In order to improve the specific activity of Pt, alternative and cheap techniques are under investigation. Therefore, in this work the performances of Pt/C samples deposited by dipping method and spray coating method have been compared, using a commercial system, as reference. Experimental tests were performed using a commercial Pt/C catalyst (20 wt. % Pt on Carbon Vulcan XC-72) deposited on Nafion membrane and tested in the 100 cm2 single-cell testing kits. At the same cell voltage (0.3 V) and Pt loading (0.12 mgPt cm-2), the results showed that the spray coating provided both a higher current density and a higher maximum power density (90 mW·cm-2) compared to the dipping method (38 mW·cm-2). Subsequently, the influence of Pt/C electrocatalyst load on PEM by spray coating method has been investigated and a Pt loading equal to 0.12 mgPt·cm-2 has guaranteed the best performances. Moreover, the performances of a commercial PEM containing a Nafion membrane functionalized by screen printing method with 0.5 mgPt·cm-2 has been compared to the PEM with the membrane prepared by spray coating method loaded with 0.12 mgPt·cm-2. Experimental results showed that, at the same cell voltage, the PEM prepared with spray coating method allowed to obtain an electrical power higher than that obtained using commercial PEM. Finally, the use of PEM at 0.12 mgPt·cm-2 obtained by spray coating method showed a remarkable stability because there was no decrease in the generated current also for long test time (higher than 30 h).